A mutation in CTSK gene in an autosomal recessive pycnodysostosis family of Pakistani origin - Naeem, Muhammad (BioMed Central, 2009)
BACKGROUND: Pycnodysostosis is a rare autosomal recessive skeletal dysplasia characterized by short stature, osteosclerosis, acro-osteolysis, frequent fractures and skull deformities. Mutations in the gene encoding cathepsin K (CTSK), a lysosomal cysteine protease, have been found to be responsible for this disease. OBJECTIVES: To identify pathogenic mutation in a consanguineous Pakistani family with 3 affected individuals demonstrating autosomal recessive pycnodysostosis. METHODS: Genotyping of 10 members of the family, including three affected and seven unaffected individuals was carried out by using polymorphic markers D1S442, D1S498, and D1S305, which are closely linked to the CTSK gene on chromosome 1q21. To screen for mutations in the CTSK gene, all of its exons and splice junctions were PCR amplified from genomic DNA and sequenced directly in an ABI Prism 310 automated sequencer. RESULTS: Genotyping results showed linkage of the pycnodysostosis Pakistani family to the CTSK locus. Sequence analysis of the CTSK gene revealed homozygosity for a missense mutation (A277V) in the affected individuals. CONCLUSION: We describe a missense mutation in the CTSK gene in a Pakistani family affected with autosomal recessive pycnodysostosis. Our study strengthens the role of this particular mutation in the pathogenesis of pycnodysostosis and suggests its prevalence in Pakistani patients.